Preliminary study on the efficacy of rituximab in the treatment of idiopathic membranous nephropathy: A single-centre experience - Chen, Ping; Mao, Min; Wang, Chendan; Zhang, Xu; Zhao, Xiaoyu; Gao, Yuanyuan; Luo, Yankun; Zhou, Yun (Frontiers in Endocrinology, 2023)
Objective: To investigate the efficacy of rituximab in the treatment of idiopathic membranous nephropathy (IMN). Methods: A total of 77 patients with IMN diagnosed in both our hospital and other hospitals were included in this study; the patients were divided into two groups: a treatment-naïve group (n = 19) and a refractory/relapsed group (n = 58). The clinical data of the patients, including urine examination, blood test, safety evaluation and efficacy evaluation results, were analysed retrospectively. The changes in clinical biochemical indexes and adverse reactions were compared between the two groups before and after treatment, and the clinical efficacy of rituximab (RTX) in the treatment of primary IMN and refractory recurrent membranous nephropathy was evaluated. Results: Of the 77 patients included in this study, the average age was 48 years, and there was a male-to-female ratio of 61:16. There were 19 cases in the initial treatment group and 58 cases in the refractory/relapse group. The 24-hour urine protein quantification, cholesterol, B cell count and M-type phospholipase A2 receptor (PLA2R) results in the 77 patients with IMN after treatment were all lower than those before treatment, and the differences were statistically significant (P < 0.05). Serum albumin was higher than before treatment, and the difference was statistically significant (P < 0.05). The total remission rate in the initial and refractory/relapsed treatment groups was 84.21% and 82.76%, respectively. There was no statistical difference in the total remission rate between the two groups (P > 0.05). During treatment, nine patients (11.69%) experienced infusion-related adverse reactions, which were relieved rapidly after symptomatic treatment. The anti-PLA2R antibody titre of the refractory/relapsed group was significantly negatively correlated with serum creatinine (r = −0.187, P = 0.045) and significantly correlated with 24-hour urine protein (r = −0.490, P < 0.001). There was a positive correlation and a significant negative correlation with serum albumin (r = −0.558, P < 0.001). Conclusions: Regardless of whether RTX is used as an initial therapy or refractory/relapsed membranous nephropathy, most patients with IMN have complete or partial remission after RTX treatment, with mild adverse reactions.